Microenvironment-responsive phosphorescence carbon dots for infection visualization and wound regeneration - Meng Xue; Jiahui Tan; Zhiheng Li; Jiayi Chen; Lingling Qiu; Bing Qi; Yunyun Zhang; Yurong Wei; Xuewen He; Jie Wang (Analytica Chimica Acta, 2026)

Thallium isotopic compositions reveal a significant contribution of thallium in soils from natural weathering processes - Yinyin Lu; Ruoxuan Qiu; Hangfei Guo; Dieyu Chen; Zicong Tan; Pei Li; Yurong Gao; Jin Wang; Juan Liu (Applied Geochemistry, 2026)

A novel particle swarm optimizer with failure-aware searching framework for neural mass model inversion - Han Li; Yang Zou; Jiyu Tan; Zihao Jia; Yurong Li; Nianyin Zeng (Swarm and Evolutionary Computation, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

Microplastics, the gut microbiome and ageing: mechanisms and intervention strategies - Zixuan Li; Yuxin Li; Tan Yurong; Wu Guojun (Environmental Geochemistry and Health, 2026)

Enhancing transferability of foliar trait retrieval models: A comparative analysis of transfer learning strategies and domain shift characterization - Yurong Huang; Nanfeng Liu; Wenqian Chen; Wei Tan; Yujia Deng; Zhihui Wang; Adam Chlus; Jian Shen; Philip A. Townsend (Remote Sensing of Environment, 2026)

Geographical-XGBoost and SHAP reveal ecosystem service supply-demand responses to landscape patterns in karst regions - Yurong Han; Jiayi Yin; Dayun Zhu; Jiaying Tan; Yingshan Zhao; Wanqing Liu; Yurong Mu (Journal of Environmental Management, 2026)

Amplifying self-protective room-temperature phosphorescence in carbon dots via electronic-state engineering - Jiahui Tan; Lin Cui; Jian Lei; Jiayi Chen; Yurong Wei; Zhigang Ren; Jie Wang (Chemical Engineering Journal, 2026)

Comparison of the centennial spatiotemporal evolution of rainfall erosivity in the top three global karst regions - Wanqing Liu; Dayun Zhu; Yingshan Zhao; Yurong Han; Jiaying Tan; Jiayi Yin (Journal of Hydrology, 2026)

Soil aggregates stability is evidently enhanced by super-binding of the N-terminal disordered tail of glomalin to soil minerals - Minghui Jia; Youchao Wang; Jin He; Shan-Ho Chou; Dehua Luo; Linchuan Fang; Jingtao Hou; Yuke Fan; Wenjun Zhang; Hansong Chen; Dejian Zhou; Yurong Liu; et al. (Soil Biology and Biochemistry, 2025)

Molecular mechanisms of HCMV-driven vascular remodeling and its significance in cardiovascular diseases - Yirui Ning; Yuhan Zhang; Huiyu Wang; Yurong Tan; Guojun Wu (Archives of Microbiology, 2025)

Antigelation spinning method to fabricate liquid crystal elastomer fibers with high orientation and reliable actuation for biomimetic devices - Xulian Hu; Chuhao Ma; Jiazhao Tan; Shaoji Wu; Caihong Gong; Wanjiang Li; Zhiming Qiu; Yurong Yan (Chemical Engineering Journal, 2025)

The Central Role of NRF2 in Cancer Metabolism and Redox Signaling: Novel Insights into Crosstalk with ER Stress and Therapeutic Modulation - Amie N. Joof; Ousman Bajinka; Yan Zhou; Fangyuan Ren; Yurong Tan (Cell Biochemistry and Biophysics, 2025)

Rapid Identification of Soybean SC15 Resistance Locus to Soybean Mosaic Virus by BSA-seq - Xiangmin Tang; Gang Jin; Huaizhu Chen; Zhaoyan Cai; Zhenguang Lai; Qingyuan Wei; Kai Li; Haijian Zhi; Yurong Tan; Dongliang Chen; Weiying Zeng; Shouzhen Yang (Plant Molecular Biology Reporter, 2025)

Transformative effects of homo-valence ion doping on persistent luminescence nanophosphors for radiotherapy monitoring - Ziyun Miao; Pei Xu; Yurong Wei; Jiahui Tan; Zhenwei Liu; Jie Pan; Lin Shi; Yong Wang; Jie Wang (Chemical Engineering Journal, 2025)

ACSL4 accelerates osteosarcoma progression via modulating TGF-β/Smad2 signaling pathway - Xiaofeng Li; Qianfen Chen; Duo Zhao; Jianshi Tan; Rongbo Liao; Yurong Gu; Jinwei Zhu; Huying Zhang; Jian Xie; Lu Chen (Molecular and Cellular Biochemistry, 2025)
Osteosarcoma (OS) is a malignant bone sarcoma arising from mesenchymal stem cells. The biological role of Acyl-CoA synthetase long-chain family member 4 (ACSL4), recently identified as an oncogene in numerous tumor types, remains largely unclear in OS. In this study, we investigated the expression of ACSL4 in OS tissues using immunohistochemistry staining (IHC) staining of a human tissue microarray and in OS cells by qPCR assay. Our findings revealed a significant up-regulation of ACSL4 in both OS tissues and cells. To further understand its biological effects, we conducted a series of loss-of-function experiments using ACSL4-depleted MNNG/HOS and U-2OS cell lines, focusing on OS cell proliferation, migration, and apoptosis in vitro. Our results demonstrated that ACSL4 knockdown remarkably suppressed OS cell proliferation, arrested cells in the G2 phase, induced cell apoptosis, and inhibited cell migration. Additionally, a subcutaneous xenograft mice model was established to validate the in vivo impact of ACSL4, revealing ACSL4 silencing impaired tumor growth in the OS xenograft mice. Additionally, we discovered that ACSL4 could regulate the phosphorylation level of Smad2 through cooperative interactions, and treatment with a TGF-β inhibitor weakened the promoting effects of ACSL4 overexpression. In short, ACSL4 regulated OS progression by modulating TGF-β/Smad2 signaling pathway. These findings underscore ACSL4 as a promising therapeutic target for OS patients and contribute novel insights into the pathogenesis of OS. Graphical abstract

Deciphering microbiomes dozens of meters under our feet and their edaphoclimatic and spatial drivers - Haoran He; Jingxiong Zhou; Yunqiang Wang; Shuo Jiao; Xun Qian; Yurong Liu; Ji Liu; Ji Chen; Manuel Delgado‐Baquerizo; Albert C. Brangarí; Li Chen; Yongxing Cui; et al. (Global Change Biology, 2024)
Microbes inhabiting deep soil layers are known to be different from their counterpart in topsoil yet remain under investigation in terms of their structure, function, and how their diversity is shaped. The microbiome of deep soils (>1 m) is expected to be relatively stable and highly independent from climatic conditions. Much less is known, however, on how these microbial communities vary along climate gradients. Here, we used amplicon sequencing to investigate bacteria, archaea, and fungi along fifteen 18‐m depth profiles at 20–50‐cm intervals across contrasting aridity conditions in semi‐arid forest ecosystems of China's Loess Plateau. Our results showed that bacterial and fungal α diversity and bacterial and archaeal community similarity declined dramatically in topsoil and remained relatively stable in deep soil. Nevertheless, deep soil microbiome still showed the functional potential of N cycling, plant‐derived organic matter degradation, resource exchange, and water coordination. The deep soil microbiome had closer taxa–taxa and bacteria–fungi associations and more influence of dispersal limitation than topsoil microbiome. Geographic distance was more influential in deep soil bacteria and archaea than in topsoil. We further showed that aridity was negatively correlated with deep‐soil archaeal and fungal richness, archaeal community similarity, relative abundance of plant saprotroph, and bacteria–fungi associations, but increased the relative abundance of aerobic ammonia oxidation, manganese oxidation, and arbuscular mycorrhizal in the deep soils. Root depth, complexity, soil volumetric moisture, and clay play bridging roles in the indirect effects of aridity on microbes in deep soils. Our work indicates that, even microbial communities and nutrient cycling in deep soil are susceptible to changes in water availability, with consequences for understanding the sustainability of dryland ecosystems and the whole‐soil in response to aridification. Moreover, we propose that neglecting soil depth may underestimate the role of soil moisture in dryland ecosystems under future climate scenarios.

Pathogenicity of Salmonella During Schistosoma-Salmonella Co-infections and the Importance of the Gut Microbiota - Ousman Bajinka; Mingming Qi; Amadou Barrow; Abdoulie O. Touray; Lulu Yang; Yurong Tan (Current Microbiology, 2022)

Lhx8 promote differentiation of hippocampal neural stem/progenitor cells into cholinergic neurons in vitro - Jinhong Shi; Haoming Li; Guohua Jin; Peipei Zhu; Meiling Tian; Jianbing Qin; Xuefeng Tan; Shuqing Zhao; Fuyu Wang; Yurong Hua; Yong Xiao (In Vitro Cellular & Developmental Biology - Animal, 2012)